2023
DOI: 10.3390/children10050766
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Prevalence of Multisystem Inflammatory Syndrome in Children (MIS-C) in Southern Italy

Abstract: Multisystem inflammatory syndrome in children (MIS-C) is a pediatric hyperinflammatory syndrome related to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection whose epidemiology is not very well known at present. The objective of the study was to better understand the incidence of MIS-C in the Apulia region in southern Italy. Our primary goal was to estimate the incidence of newly identified cases of MIS-C in children aged 0–18 years, during a period of six months, encompassing the second pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…However, our findings are subject to several limitations. First, while our sample size is larger than some of the previous studies, 38,39 it remains relatively small, which may limit the generalizability of our findings and precluded us from performing a more comprehensive, multivariate analysis. Second, we may have overestimated the MIS-C incidence due to underreporting of mild/asymptomatic pediatric COVID-19 cases, especially during the Omicron period when contact tracing was less rigorous.…”
Section: T a B L E 3 (Continued)mentioning
confidence: 88%
“…However, our findings are subject to several limitations. First, while our sample size is larger than some of the previous studies, 38,39 it remains relatively small, which may limit the generalizability of our findings and precluded us from performing a more comprehensive, multivariate analysis. Second, we may have overestimated the MIS-C incidence due to underreporting of mild/asymptomatic pediatric COVID-19 cases, especially during the Omicron period when contact tracing was less rigorous.…”
Section: T a B L E 3 (Continued)mentioning
confidence: 88%
“…The reported incidence of MAS was 1.9% (12/638) for KD, 3.2% (8/247) for incomplete KD, 4.8% (3/63) for KDSS, and 6.3% (4/63) for refractory KD [ 22 ]. In patients with MIS-C, the incidence of MAS has been reported to be much higher at 22.7% (5/22) [ 6 ], 42.1% (8/19) [ 9 ], and 50.0% (5/10) [ 3 ]. Rodriguez-Smith et al [ 9 ] reported that patients with MIS-C who met the 2016 MAS criteria had significantly higher levels of interferon-related chemokines than did patients with MIS-C who did not meet the 2016 MAS criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Soon after, similar cases began to be reported in the United Kingdom, Spain, France, the United States, India, Brazil, and many other countries, including Korea [ 2 , 4 ]. The condition is now called COVID-19-associated multisystem inflammatory syndrome in children (MIS-C) or pediatric inflammatory multisystem syndrome temporarily related to SARS-CoV-2 (PIMS-TS) [ 4 , 5 , 6 ]. MIS-C is a serious complication that can occur two to eight weeks after SARS-CoV-2 infection and is characterized by infectious triggers, systemic inflammation, and organ dysfunction [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first epidemiological study of MIS-C in Europe showed a cumulative incidence of 3.27 per 100,000 inhabitants and a prevalence of 74 cases per 100,000 pediatric subjects with previous SARS-CoV-2, between 0 and 18 years of age. A higher incidence of gastrointestinal and cardiac involvement has been demonstrated with myocarditis compared with Kawasaki disease [13].…”
Section: Introductionmentioning
confidence: 99%